Evaluation of Mannose Binding Lectin Gene Variants in Pediatric Influenza Virus-Related Critical Illness - Levy, Emily R.; Yip, Wai-Ki; Super, Michael; Ferdinands, Jill M.; Mistry, Anushay J.; Newhams, Margaret M.; Zhang, Yu; Su, Helen C.; McLaughlin, Gwenn E.; Sapru, Anil; Loftis, Laura L.; Weiss, Scott L.; et al. (Frontiers in Immunology, 2019)
Background: Mannose-binding lectin (MBL) is an innate immune protein with strong biologic plausibility for protecting against influenza virus-related sepsis and bacterial coinfection. In an autopsy cohort of 105 influenza-infected young people, carriage of the deleterious MBL gene MBL2_Gly54Asp(“B”) mutation was identified in 5 of 8 individuals that died from influenza-methicillin-resistant Staphylococcus aureus (MRSA) coinfection. We evaluated MBL2 variants known to influence MBL levels with pediatric influenza-related critical illness susceptibility and/or severity including with bacterial coinfections. Methods: We enrolled children and adolescents with laboratory-confirmed influenza infection across 38 pediatric intensive care units from November 2008 to June 2016. We sequenced MBL2 “low-producer” variants rs11003125(“H/L”), rs7096206(“Y/X”), rs1800450Gly54Asp(“B”), rs1800451Gly57Glu(“C”), rs5030737Arg52Cys(“D”) in patients and biologic parents. We measured serum levels and compared complement activity in low-producing homozygotes (“B/B”, “C/C”) to HYA/HYA controls. We used a population control of 1,142 healthy children and also analyzed family trios (PBAT/HBAT) to evaluate disease susceptibility, and nested case-control analyses to evaluate severity. Results: We genotyped 420 patients with confirmed influenza-related sepsis: 159 (38%) had acute lung injury (ALI), 165 (39%) septic shock, and 30 (7%) died. Although bacterial coinfection was diagnosed in 133 patients (32%), only MRSA coinfection (n=33, 8% overall) was associated with death (p<0.0001), present in 11 of 30 children that died (37%). MBL2 variants predicted serum levels and complement activation as expected. We found no association between influenza-related critical illness susceptibility and MBL2 variants using family trios (633 biologic parents) or compared to population controls. MBL2 variants were not associated with admission illness severity, septic shock, ALI, or bacterial coinfection diagnosis. Carriage of low-MBL producing MBL2 variants was not a risk factor for mortality, but children that died did have higher carriage of one or more B alleles (OR 2.3; p=0.007), including 7 of 11 with influenza MRSA-related death (versus 2 of 22 survivors: OR 14.5, p=0.0002). Conclusions: MBL2 variants that decrease MBL levels were not associated with susceptibility to pediatric influenza-related critical illness or with multiple measures of critical illness severity. We confirmed a prior report of higher B allele carriage in a relatively small number of young individuals with influenza-MRSA associated death.